1979
DOI: 10.1203/00006450-197908000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Limited Left Ventricular Response to Volume Overload in the Neonatal Period: a Comparative Study with the Adult Animal

Abstract: Cardiac dimensions fetus cardiac function newborn cardiac output ventricular compliance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(63 citation statements)
references
References 7 publications
2
61
0
Order By: Relevance
“…The saline infusion in preterm lambs with closed ductus produced a significant increase in stroke volume. The response differed from that observed in lamb fetuses at the same gestational age (8)(9)(10)(11)(12), but was similar to that seen in full-term newborn (6) and I-wk-old lambs (3)(4)(5)7). Although a Frank-Starling relationship has been demonstrated in the fetal lamb (28), challenging the fetus with a volume load only modestly increases stroke volume above baseline measurements (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The saline infusion in preterm lambs with closed ductus produced a significant increase in stroke volume. The response differed from that observed in lamb fetuses at the same gestational age (8)(9)(10)(11)(12), but was similar to that seen in full-term newborn (6) and I-wk-old lambs (3)(4)(5)7). Although a Frank-Starling relationship has been demonstrated in the fetal lamb (28), challenging the fetus with a volume load only modestly increases stroke volume above baseline measurements (8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 53%
“…Perhaps this increase in contractility when the ductus is open persists during the volume infusion and plays a role in the increased output observed during that condition. However, other studies in adult and newborn animals have not demonstrated an increase in left ventricular contractility during a volume infusion (5,6,30).…”
Section: Discussionmentioning
confidence: 97%
“…1A). Furthermore, the neonatal LV has a smaller twist amplitude coupled with slower and delayed untwisting when compared with older children and adults (23), which may reduce the contribution of LV untwisting/suction to early diastolic filling.Invasive animal studies that have explored the functional maturation of the neonatal LV within the first weeks of life (4, 27, 30), including its response to preload (2,19,28), also support the current assumption that the neonatal LV may have relatively less diastolic reserve when faced with altered loading conditions. The impact of atrial tachycardia on neonatal LV function, a common finding in the critically ill neonate, and a state that is poorly tolerated by the more mature heart with diastolic dysfunction in part as tachycardia reduces diastolic filling time (36), has been minimally examined.…”
mentioning
confidence: 90%
“…Consequently, its output need not be as high as that of the newborn left ventricle (1)(2)(3)(4). At birth, when oxygen demand increases dramatically and the systemic and pulmonary circulations separate, left ventricular output increases threefold (5)(6)(7)(8)(9)(10)(11)(12). However, studies performed in sheep suggest that the fetal left ventricle is incapable of increasing its output anywhere near levels seen in the newborn; maximal increases are less than 50% above control in response to increases in preload (13) or heart rate (14,15), or during {J-adrenergic stimulation (16).…”
mentioning
confidence: 99%